Improving the Logistics of Institutional Postal Services - Nagy, Pálma Eszter; Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2023)
Postal services are often considered by the different institutions as a back-up service. Taking into account that in case of large geographical coverage these services can generate significant costs, it is important to optimize the postal service functions within these institutions and to develop the already existing conventional postal services. Within the frame of this article the authors review the logistics processes of the postal services at the University of Miskolc to propose improvements to the processes of postal services focusing on delivery. The main regulatory elements and the logistics processes of the institutional postal services are discussed and some critical remarks are described focusing on three main areas: the facility location optimization of the institutional postal services, the lack of use of modern technologies and the lack of modern administrative facilities. On the basis of these criticisms, the authors define recommendations for improving institutional postal services. Regarding the facility location optimization problem, a mathematical model and an optimization algorithm is described to evaluate the efficiency of the logistics processes of delivery services. The proposed methodology supports a cost-based analysis of different solution variants and a priority-based differentiation between institutions and offices. The suggested approach is tested with a real scenario, where the numerical results validate the efficiency of the evaluation of optimization algorithm. The second improvement direction is the application of a pneumatic tube system. The authors show the most important parts of the proposed pneumatic tube system, which can lead to decreased labor cost and increased service level.